On the use of voltage stability index to prevent undesirable distance relay operation during voltage instability - Kamariah Sahalihudin, 1987-; Azhar Khairuddin, 1963-; Fakulti Kejuruteraan Elektrik (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2011